Prospective multicentre cohort study of transthoracic echocardiography provision in the South West of the UK during the first wave of SARS-CoV-2 pandemic. Issue 1 (27th January 2021) - Crook, Rebecca Lucy; Williams, Howell; Green, Mary; Brown, Stewart; Morris, Richard; Fletcher, Hannah; Walters, Sarah; Walsh, Catherine; Price, Anna; King, Samantha; McAloon, Christopher James
Abstract : Aims: It was predicted internationally that transthoracic echocardiography (TTE) would be vital during the SARS-CoV-2 outbreak. We therefore, designed a study to report the demand for TTE in two large District General Hospitals during the rise in the first wave of the SARS-CoV-2 pandemic in the UK. A primary clinical outcome of 30-day mortality was also assessed. Methods: The TTE service across two hospitals was reconfigured to maximise access to inpatient scanning. All TTEs of suspected or confirmed SARS-CoV-2 patients over a 3-week period were included in the study. All patients were followed up until at least day 30 after their scan at which point the primary clinical outcome of mortality was recorded. Comparative analysis based on mortality was conducted for all TTE results, biochemical markers and demographics. Results: 27 patients with confirmed SARS-CoV-2 had a TTE within the inclusion window. Mortality comparative analysis showed the deceased group were significantly older (mean 68.4, SD 11.9 vs 60.5, SD 13.0, p=0.03) and more commonly reported fatigue in their presenting symptoms (29.6% vs 71.4%, p=0.01). No other differences were identified in the demographic or biochemical data. Left ventricular systolic dysfunction was noted in 7.4% of patients and right ventricular impairment or dilation was seen in 18.5% patients. TTE results were not significantly different in mortality comparative analysis. Conclusion: This study demonstrates an achievable approach to TTE services when under increased pressure. Data analysis supports the limited available data suggesting right ventricular abnormalities are the most commonly identified echocardiographic change in SARS-CoV-2 patients. No association can be demonstrated between mortality and TTE results.